Organic–Inorganic Hybrid Passivation Enables Perovskite QLEDs with an EQE of 16.48%. Issue 50 (10th October 2018) - Song, Jizhong; Fang, Tao; Li, Jianhai; Xu, Leimeng; Zhang, Fengjuan; Han, Boning; Shan, Qingsong; Zeng, Haibo
Abstract: Perovskite quantum dots (QDs) with high photoluminescence quantum yields (PLQYs) and narrow emission peak hold promise for next‐generation flexible and high‐definition displays. However, perovskite QD films often suffer from low PLQYs due to the dynamic characteristics between the QD's surface and organic ligands and inefficient electrical transportation resulting from long hydrocarbon organic ligands as highly insulating barrier, which impair the ensuing device performance. Here, a general organic–inorganic hybrid ligand (OIHL) strategy is reported on to passivate perovskite QDs for highly efficient electroluminescent devices. Films based on QDs through OIHLs exhibit enhanced radiative recombination and effective electrical transportation properties compared to the primal QDs. After the OIHL passivation, QD‐based light‐emitting diodes (QLEDs) exhibit a maximum peak external quantum efficiency (EQE) of 16.48%, which is the most efficient electroluminescent device in the field of perovskite‐based LEDs up to date. The proposed OIHL passivation strategy positions perovskite QDs as an extremely promising prospect in future applications of high‐definition displays, high‐quality lightings, as well as solar cells. Abstract : Highly efficient perovskite quantum‐dot light‐emitting diodes (QLEDs) through organic–inorganic hybrid ligand (OIHL) passivation strategy are reported. The OIHL‐passivated films exhibit enhanced radiative recombination and effective electrical transportation features, which make QLEDs have a maximum peak external quantum efficiency (EQE) of 16.48%, which is the most efficient in the field of perovskite‐based LEDs up to now.